Indium-MOF as Multifunctional Promoter to Remove Ionic Conductivity and Electrochemical Stability Constraints on Fluoropolymer Electrolytes for All-Solid-State Lithium Metal Battery - Liu, Xiong Xiong; Pan, Long; Zhang, Haotian; Liu, Cancan; Cao, Mufan; Gao, Min; Zhang, Yuan; Xu, Zeyuan; Wang, Yaping; Sun, ZhengMing (Nano-Micro Letters, 2025)
Fluoropolymers promise all-solid-state lithium metal batteries (ASLMBs) but suffer from two critical challenges. The first is the trade-off between ionic conductivity (σ) and lithium anode reactions, closely related to high-content residual solvents. The second, usually consciously overlooked, is the fluoropolymer’s inherent instability against alkaline lithium anodes. Here, we propose indium-based metal–organic frameworks (In-MOFs) as a multifunctional promoter to simultaneously address these two challenges, using poly(vinylidene fluoride–hexafluoropropylene) (PVH) as the typical fluoropolymer. In-MOF plays a trio: (1) adsorbing and converting free residual solvents into bonded states to prevent their side reactions with lithium anodes while retaining their advantages on Li+ transport; (2) forming inorganic-rich solid electrolyte interphase layers to prevent PVH from reacting with lithium anodes and promote uniform lithium deposition without dendrite growth; (3) reducing PVH crystallinity and promoting Li-salt dissociation. Therefore, the resulting PVH/In-MOF (PVH-IM) showcases excellent electrochemical stability against lithium anodes, delivering a 5550 h cycling at 0.2 mA cm−2 with a remarkable cumulative lithium deposition capacity of 1110 mAh cm−2. It also exhibits an ultrahigh σ of 1.23 × 10−3 S cm−1 at 25 °C. Moreover, all-solid-state LiFePO4|PVH-IM|Li full cells show outstanding rate capability and cyclability (80.0% capacity retention after 280 cycles at 0.5C), demonstrating high potential for practical ASLMBs. Highlights: 1 Indium-based metal–organic framework (In-MOF) is proposed as a multifunctional promoter to create poly(vinylidene fluoride–hexafluoropropylene) (PVH)/In-MOF (PVH-IM) composite solid polymer electrolyte, synchronously achieving a high ionic conductivity of 1.23 × 10−3 S cm−1 and excellent electrochemical stability against Li anodes. 2 In-MOF not only can adsorb and convert free residual solvents into bonded states to prevent their side reactions with Li anodes, but also induce inorganic-rich solid electrolyte interphase layers to prevent PVH from reacting with lithium anodes and promote uniform lithium deposition without dendrite growths. 3 The Li|PVH-IM|Li symmetric cells maintain stable cycling for 5550 h at the current density of 0.2 mA cm−2. In addition, all-solid-state LFP|PVH-IM|Li full cells deliver a significant capacity retention of 80.0% at a rate of 0.5C after 280 cycles at 25 °C.